Análise do sistema orçamentário na priorização de políticas públicas “secundárias”: o caso de um município paranaense de pequeno porte - Dornellas, Eduardo Dias (2015)
Considering the limitation of financial and budgetary resources by the State, whose origin is in the collection and the public entity's indebtedness, the transparency in public spending and the proper application of budget resources constitute obligations in the exercise of public management. Therefore, this case study analyzed the budgetary parts aiming to Planning and Local and Regional Development. This case study analyzed the budgetary parts in the small municipality of Adrianópolis, situated in the Vale do Ribeira is region, imbricated between the state of Paraná and São Paulo, during the term of Pluriannual Plans 2006 to 2009 and 2010 to 2013, having the budgetary execution as a tool for prioritizing secondary public policies – those without application’s enforcement of Constitutional minimum. Believing there is a paradox between public planning and budgetary execution, this study sought to answer the following problem: which areas of public planning are prioritized as secondary public policies? The methodology was based on applied research, qualitative – descriptive and exploratory, that searched in the official accounting data – specifically in the Summarized Report of Budget Execution (RREO), on the Pluriannual Plan (PPA) and the Annual Budgetary Law (LOA) – the effectiveness of public actions in different areas, functions and sub-functions assigned with budget allocations, featuring public spending and the provision of goods and services to the population. The results confirmed the effectiveness of the proposed instrument, identifying the prioritization of secondary public policies in a hierarchical fashion and pointed a misalignment between budget parts.